Antioxidant Activity of Astaxanthin Flour Extract of Mud Crab (Scylla Serrata) with Different Acetone Concentrations. Issue 1 (March 2021) - Karnila, R.; Edison; Ramadhani, N. R.
Abstract: Mud crabis one of Indonesia's economically valuable fishery commodities, the high demand for crab from world and domestic trade will have an impact on the resulting waste in the form of shell waste. Crab shells contain bioactive compounds that have the potential to be antioxidant astaxanthin. This study consisted of four stages, namely (1) astaxanthin extraction (2) yield (3) terpenoid test (4) antioxidant test (DPPH). The objectives of this study were (1) to determine the amount of astaxanthin yield, (2) to determine the terpenoid test, (3) to determine the potential for antioxidant activity in mangrove crabs. The data obtained were tabulated in the form of tables and graphs, which were analyzed descriptively. The results showed that the yield with different acetone concentrations produced the highest yield of A 65%, namely 4.46 g, A 50%, namely 3.36 g and A 80% in the amount of 1.71 g. The antioxidant activity showed that treatment with the concentration of acetone extraction was able to produce the IC value of50 lowestwith acetone concentration of 65% compared to the extraction concentration of 50%. The ICvalue50 of 805.837 ug / mL is still classified as having weak or inactive antioxidant activity.